The Effect of the Phospholipid Bilayer Environment on Cholesterol Crystal Polymorphism. Issue 4 (6th February 2019) - Varsano, Neta; Beghi, Fabio; Dadosh, Tali; Elad, Nadav; Pereiro, Eva; Haran, Gilad; Leiserowitz, Leslie; Addadi, Lia
Abstract: Cholesterol crystallization from mixtures of unesterified cholesterol with phospholipids and cholesterol esters is believed to be a key event in atherosclerosis progression. Not much is understood, however, about the influence of the lipid environment on cholesterol crystallization. Here we study cholesterol monohydrate crystal formation from mixed bilayers with palmitoyl‐oleoyl‐phosphatidylcholine (POPC), dipalmitoyl‐phosphatidylcholine (DPPC) and sphingomyelin. We show that disordered phospholipids and sphingomyelin stabilize the formation of crystal plates of the triclinic cholesterol monohydrate polymorph, whereas saturated glycerolipids stabilize helical and tubular crystals of the metastable monoclinic polymorph. We followed the subsequent transformation of these helical crystals into the stable triclinic plates. Discovering the relations between membrane lipid composition and cholesterol crystal polymorphism may provide important clues to the understanding of cholesterol crystal formation in atherosclerosis. Abstract : The chemical environment of phospholipid bilayers affects the formation of cholesterol crystals, leading to the precipitation of different crystal morphologies. This work highlights the tendency of sphingomyelin and disordered glycerophospholipids to stabilize triclinic plate cholesterol monohydrate crystals, while saturated glycerophospholipids give rise to metastable monoclinic helical and tubular structures that transform into plates at a mature stage (see figure).